2004
DOI: 10.1007/978-3-540-30208-7_143
|View full text |Cite
|
Sign up to set email alerts
|

MammoGrid: A Service Oriented Architecture Based Medical Grid Application

Abstract: The MammoGrid project has recently delivered its first proof-of-concept prototype using a Service-Oriented Architecture (SOA)-based Grid application to enable distributed computing spanning national borders. The underlying AliEn Grid infrastructure has been selected because of its practicality and because of its emergence as a potential open source standards-based solution for managing and coordinating distributed resources. The resultant prototype is expected to harness the use of huge amounts of medical imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…NeuGRID exploits the experience developed during the earlier FP5 MammoGrid project (this provided knowledge related to the middleware and upperware that allowed specific applications to 'talk' to the Grid while remaining independent) [43][44][45][46][47][48], and the AddNeuroMed study (the collection, archiving and retrieval of multicenter clinical data, biomedical images and computerized image analysis) from the FP6 InnoMed project.…”
Section: Neugrid's Gridmentioning
confidence: 99%
See 1 more Smart Citation
“…NeuGRID exploits the experience developed during the earlier FP5 MammoGrid project (this provided knowledge related to the middleware and upperware that allowed specific applications to 'talk' to the Grid while remaining independent) [43][44][45][46][47][48], and the AddNeuroMed study (the collection, archiving and retrieval of multicenter clinical data, biomedical images and computerized image analysis) from the FP6 InnoMed project.…”
Section: Neugrid's Gridmentioning
confidence: 99%
“…A SOA separates functions into distinct units termed services [53]. The MammoGrid project proposed perhaps the first healthcare example of a Grid-based SOA [43]. The MammoGrid philosophy was to provide a set of services that were i ndependent both of the front-end clinician-facing software and of the back-end Grid-facing software.…”
Section: Neugrid Architecturementioning
confidence: 99%
“…This research advocates the use of semantic grid services to medical applications and more specifically to medical images. Some examples of work being done in the area of semantic grid services can be seen in the following references: [4]; [10]; [22]; [53].…”
Section: Knowledge and Semantic Gridmentioning
confidence: 99%
“…It is a concept that hinges on using grid services to federate a collection of heterogeneous data bases for medical images analysis [4].…”
Section: Federation Of Gridsmentioning
confidence: 99%
“…Also, they have proven to be a reliable and efficient distributed infrastructure for the management of medical images. A number of grid projects and developments in the biomedical area include: the European mammogram database MammoGrid, 4 the biomedical platform MedIGrid, 5 Virtual-PACS (a grid client application for the digital imaging and communications in medicine [DICOM] DataService), 6 caGrid (an open source grid software infrastructure aimed at enabling multi-institutional data sharing and analysis originated at the NCI Cancer Biomedical Informatics Grid [caBIG™]), 7 and the European grid-based pediatrics platform Health-e-Child, 8 among others. In addition, several research projects, focused on the augmented computing power of grids, have been reported in applications such as radiation therapy dosimetry planning through Monte Carlo simulations, 1 multiple sclerosis brain segmentation, 9 and tomographic image reconstruction.…”
Section: Introductionmentioning
confidence: 99%